Potential of Socialization of Students at Classical Universities of Russia - Irina Leonidovna Sizova; Alena Vasilyevna Yermilova; Timur Maratovich Husyainov (Управленческое консультирование)
In the article the concept (based on P. Bourdieu's ideas), a collective habitus of the higher school and its assimilation by students in modern Russia is built. Using the original questionnaire, authors tried to open in the empirical way its basic properties and to simulate habitus of social humanity faculty of one of classical universities of the country.